2018
DOI: 10.22159/ajpcr.2018.v11i1.19430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenolic Acids and Antioxidant Activities of Young and Mature Leaves of Tectona Grandis L F

Abstract: Objective: The present study aims in comparison of phenolic acids and its antioxidant potentialities of young and mature leaf extract of Tectona grandis L f. Methods:Various phenolic acids present in methanolic leaf extract of young and mature leaves of T. grandis were analyzed by reversed-phase highperformance liquid chromatography analysis. The antioxidant potentiality of the extracts was determined by various analytical methods such as 2,2-diphenyl-1-picrylhydrazyl, ferric reducing/antioxidant power, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…These compounds force together to reduce free radicals. Murukan and Murugan (2018c) reported that methanolic leaf extracts of young and mature leaf of T. grandis has phenolic compounds such as gallic, vanillic, p-hydroxybenzoic, ferulic, chlorogenic, sinapic, p-coumarate, and cinnamic acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds force together to reduce free radicals. Murukan and Murugan (2018c) reported that methanolic leaf extracts of young and mature leaf of T. grandis has phenolic compounds such as gallic, vanillic, p-hydroxybenzoic, ferulic, chlorogenic, sinapic, p-coumarate, and cinnamic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Teak leaves content secondary metabolites such as flavonoids, alkaloids, tannins, anthraquinones, naphthoquinone, anthocyanins and cyanidins which have various activities, such as antibacterial, antitoxic and antioxidant activity (Murukan and Murugan 2018a, Murukan and Murugan 2018b, Murukan and Murugan 2018cand Arief et al 2014. The green young teak leaves turn to brownish-red color when they are ripped.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados tabulados en el Cuadro 1 son similares a los obtenidos en trabajos previos [23], donde se reporta la inhibición del radical DPPH en un 60,31% utilizando extractos foliares de M. gangitica, haciendo énfasis en que la actividad antioxidante de los extractos fue superior a aquella obtenida con soluciones de ácido ascórbico a 100 µg mL -1 , lo cual fue relacionado con la concentración de polifenoles en los extractos. Así mismo, se ha obtenido correlación positiva alta (R 2 =0,907) entre la concentración de polifenoles en extractos foliares de I. batatas y la actividad antioxidante de los mismos [36], lo que coincide con otros reportes [39,54,55,56], donde se señala la relación entre un mayor contenido de compuestos fenólicos y la alta actividad antioxidante de extractos vegetales.…”
Section: Actividad Antioxidanteunclassified
“…For the example, plant maturity and harvest timing is required to ensure the efficiency of production in the term of yield as well as the optimum amount of phytochemical and physicochemical in the plant. Murukan and Murukan, (2018) determined the young leaf extract exhibited potent antioxidant potentiality when compared with the mature leaf extract of Tectona grandis. Chang et al, (2018) study about polyphenolics profile and antioxidant activity in each of Clausena lansium leaf development stages such as leaf buds, young, mature and old leaves, and the result shows old leaves was selected as an economical sources of bioactive compounds which can be applied in nutraceutical and pharmaceutical product.…”
Section: Introductionmentioning
confidence: 99%